Industrial Robot Automation in Solving Non-Vacuum Electron-Beam Welding Problems; MATEC Web of Conferences; Vol. 79 : Information-Measuring Equipment and Technologies (IME&T 2016) - Borovik V. Vasiliy; Shatravin V. Vladislav; Junusov I. Il'jas; Shashev D. Dmitri; Kornilov S. Sergei; Rempe N. Nikolai; Shidlovskiy S. V. Stanislav Viktorovich (2016, 2016)
Title screen